Recent Trends in Eco-Friendly Materials for Agrochemical Pollutants Removal: Polysaccharide-Based Nanocomposite Materials - Baigorria, Estefanía [UNESP]; Sanchez, Laura M.; Primiano, Romina P. Ollier; Alvarez, Vera A. (My University, 2023)
The excessive use of pesticides in modern agriculture as a result of the increasing demand for crops for the world's growing population has caused harmful effects not only to human health but also to the environment. In this context, great efforts have been recently made to develop novel low-cost and eco-friendly technologies for the removal of pesticides from contaminated environments. Various adsorbent materials having eco-friendly and sustainable characteristics are effective in removing harmful pesticide residues from wastewater, such as nanostructured bio-polymeric ones. Among biopolymers, polysaccharides have emerged as some interesting sustainable alternatives as a direct consequence of some intrinsic advantages, such as their non-toxicity, biocompatibility, and biodegradability, as well as their extensive availability and the associated low-production costs. Moreover, polysaccharides can be easily functionalized and cross-linked (chemically or physically), which makes them a versatile and promising approach for the production of a wide variety of materials such as micro- and nanoparticles, membranes, hydrogels, etc. Cellulose, alginate, chitosan, and guar gum are some of the numerous polysaccharides that can be employed. In this chapter, recent progress on the investigation of polysaccharide-based nanocomposite materials for pesticide adsorption from wastewater is critically reviewed. The main properties and characteristics of the nanocomposites, as well as their adsorption performance towards several types of pesticides are analyzed and discussed in terms of their efficiency and operability in sustainable agricultural practices.